Pengaruh Iklim Organisasi dan Kepuasan Kerja terhadap Inovasi Guru Paud Sekolah Guang Ming Seluruh Indonesia - Lisa Kumala Sari; Muljadi Muljadi; Isomudin Isomudin (Institut Nalanda, 2024)
This study aims to determine the effect of Organizational Climate and Job Satisfaction, either partially or simultaneously on the innovation teachers. This research is quantitative in nature with data collection carried out through the distribution of questionnaires. The data obtained were processed using linear regression analysis with the help SPSS v20. The results showed that the hypothesis of the correlation coefficient of the three variables was confirmed. It can be concluded that (1) there is a positive relationship between organizational climate and the innovation teachers. (2) there is a positive relationship between job satisfaction and the innovation teachers (3) simultaneously there is a positive relationship between organizational climate and job satisfaction with the innovation teachers (4) at 98.6% climate organization and job satisfaction affect teacher innovation, the rest is influenced by other variables outside the study (5) the correlation coefficient value is ry1.2 = 0.993, indicating that the level of relationship strength is included in the very strong category.